2019
DOI: 10.24974/amae.13.2.431
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Motherwork in the Zapotec Diaspora: Zapoteca Mothers’ Perspectives on Indigenous Language Maintenance

Abstract: This article explores Indigenous Mexican mothers’ perspectives on multilingualism and Indigenous language maintenance in their children’s lives. Drawing on interview data from a larger qualitative study of language and ideology among multilingual children in Los Angeles, California, the article examines the perspectives of four Zapotec mothers who have children in a local public school with a Spanish-English dual language program. The interview data highlight what these women think and do with respect to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In almost all the comic strips, mothers and grandmothers were central figures in the pedagogical scenes of the LPSTs. As research has shown, the work of mothers and grandmothers in language and literacy learning is integral to the experiences of racialized children (Cioè‐Peña, 2021; Martínez & Mesinas, 2019; Nuñez, 2019). Additionally, the comic strips challenge historical and contemporary deficit ideologies about Latinx students, parents, and families and their care for formal education.…”
Section: Discussionmentioning
confidence: 99%
“…In almost all the comic strips, mothers and grandmothers were central figures in the pedagogical scenes of the LPSTs. As research has shown, the work of mothers and grandmothers in language and literacy learning is integral to the experiences of racialized children (Cioè‐Peña, 2021; Martínez & Mesinas, 2019; Nuñez, 2019). Additionally, the comic strips challenge historical and contemporary deficit ideologies about Latinx students, parents, and families and their care for formal education.…”
Section: Discussionmentioning
confidence: 99%
“…The current work in education scholarship employing CLI shows its critical importance for understanding the unique positioning of Indigenous youth from Abya Yala in U.S. urban settings and schools (e.g., Casanova, 2019; Martínez, & Mesinas, 2019; Urrieta & Calderón, 2019). Moreover, a raciolinguistic perspective elucidates how racialized and languaged systems interact and travel with Indigenous migrant youth across borders.…”
Section: Analytic Frameworkmentioning
confidence: 99%
“…While my original title for this project was “Exploring and Expanding Bilingual Students’ Linguistic Repertoires in an Innovative Dual Language Program,” some of these Latinx children of immigrants very quickly informed me that they were actually multilingual. For example, two of them, Alba and Samantha, spoke an Indigenous Mexican language called Zapotec (Zapoteco), which is spoken widely by the Zapotec people in the southern Mexican state of Oaxaca, the neighboring state of Veracruz, and in various other parts of Mexico, as well as in diasporic communities in the United States (Martínez & Mesinas, 2019; Mesinas, 2021). Both Alba and Samantha are of Zapotec ancestry, and they were exposed to the Zapotec language in their homes from early childhood on.…”
Section: Learning In Dialoguementioning
confidence: 99%